Physical determinants of tennis performance in competitive teenage players - Girard, O.; Millet, G. P. (The Journal of Strength and Conditioning Research, 2009)
It is unclear how physical attributes influence tennis-specific performance in teenage players. The aims of this study were (a) to examine the relationships between speed, explosive power, leg stiffness, and muscular strength of upper and lower limbs; and (b) to determine to what extent these physical qualities relate to tournament play performance in a group of competitive teenage tennis players. A total of 12 male players aged 13.6 ± 1.4 years performed a series of physical tests: a 5-m, 10-m, and 20-m sprint; squat jump (SJ); countermovement jump (CMJ); drop jump (DJ); multi-rebound jumps; maximum voluntary contraction of isometric grip strength; and plantar flexor of the dominant and nondominant side. Speed (r = 0.69, 0.63, and 0.74 for 5-, 10-, and 20-m sprints, respectively), vertical power abilities (r = -0.71, -0.80 and -0.66 for SJ, CMJ, and DJ, respectively), and maximal strength in the dominant side (r = -0.67 and -0.73 for handgrip and plantar flexor, respectively) were significantly correlated with tennis performance. However, strength in the nondominant side (r = -0.29 and -0.42 for handgrip and plantar flexor) and leg stiffness (r = -0.15) were not correlated with the performance ranking of the players. It seems that physical attributes have a strong influence on tennis performance in this age group and that an important asymmetry is already observed. By monitoring regularly such physical abilities during puberty, the conditioning coach can modify a program to compensate for the imbalances. This would in turn minimize the risks of injuries during this critical period.